Diet quality and environmental impact of university students’ food choices at a South African university - Sahadeo, Sanrika; Naicker, Ashika; Makanjana, Onwaba; Olaitan, Oluwasiji O. (Frontiers in Nutrition, 2025)
BackgroundSouth Africa faces a triple burden of malnutrition. The country’s food system, characterized by high consumption of resource-intensive animal and processed foods, contributes significantly to greenhouse gas emissions. Global policy frameworks increasingly emphasize sustainable diets, but national strategies and implementation efforts in South Africa are still emerging. The climate emergency has amplified global efforts to promote sustainability, yet the environmental impact of dietary choices remains underexplored in South Africa. This study examines diet quality and the environmental impact of food choices of students in a South African university, offering insights into sustainability from a young consumer perspective.MethodsDietary data were collected using a repeated 24-h food recall method over two non-consecutive days, including a weekend day, for 400 students. Nutrient adequacy was assessed using the cut-off points of recommended daily allowance (RDA) and adequate intake, while diet quality and non-communicable disease (NCD) risk were evaluated using the Global Diet Quality Score (GDQS). The environmental impact of students’ diets was estimated using the Plate Up for the Planet carbon footprint calculator.ResultsMale students exceeded carbohydrate (310.8 g) and protein (88.06 g) requirements but had notable micronutrient deficiencies, including calcium (74.3% prevalence of inadequacy [POI]), magnesium (96.7% POI), and vitamin D (92.8% POI). Female students showed deficiencies in dietary fiber, calcium (94.0% POI), and folate (92.3% POI). The GDQS revealed that 99.8% of students (37.8% males, 62.0% females) were at high risk for nutrient inadequacy and non-communicable diseases (NCDs). The mean carbon footprint analysis showed that male students (5671.55CO₂e) had a higher environmental impact than females (5020.36 CO₂e).ConclusionNutrient inadequacy and poor diet quality are highly prevalent among university students, predisposing them to a high risk of NCDs and contributing to a high amount of greenhouse gas emissions. University food environments significantly influence student diets, necessitating policy interventions to promote sustainable food choices while reducing environmental impact.